RANCANG BANGUN SISTEM MONITORING PADA HIDROPONIK NFT (NURTIENT FILM TEHCNIQUE) BERBASIS IOT - Lindu Pamungkas; Pratolo Rahardjo; I Gusti Agung Putu Raka Agung (Jurnal SPEKTRUM, 2021)
The use of hydroponics is an effective way to carry out farming activities without theneed for large tracts of land. Hydroponics requires extra supervision to be able to produceplants with good quality. There are three main parameters in hydroponics, namely the amountof dissolved nutrient content, the pH level in water, and the water suhue level. To provideconvenience in conducting surveillance, this research designed an IoT-based NFT hydroponicmonitoring system. The use of TDS sensors, pH sensors, and temperatur sensors DS18B20 inthis study are used to measure any changes that occur in the three parameters. Sensor datawill be processed by Arduino Mega 2560 and sent to Firebase databases via NodeMCUESP8266 which is connected to the internet network, so users can supervise anytime andanywhere through the android mobile application.